Cytosolic accumulation of HPV16 E7 oligomers supports different transformation routes for the prototypic viral oncoprotein: The amyloid-cancer connection - Dantur, Karina Ines (2009)
E7 is the major transforming activity in human papillomaviruses, a causal agent for cervical cancer. HPV16 E7 is a small protein with a natively unfolded domain for which dozens of specific cellular targets were described, and represents a prototypical oncoprotein among small DNA tumor viruses. The protein can form spherical oligomers with amyloid-like properties and chaperone activity. Conformation specific antibodies locate endogenous oligomeric E7 species in the cytosol of 3 model cell lines, strongly colocalizing with amyloid structures and dimeric E7 localizes to the nucleus. The cytosolic oligomeric E7 appear as the most abundant species in all cell systems tested. We show that nuclear E7 levels are replenished dynamically from the cytosolic pool and do not result from protein synthesis. Our results suggest that long-term events related to de-repression of E7 would cause accumulation of excess E7 into oligomeric species in the cytosol. These, together with the known target promiscuity of E7, may allow interactions with many of the non-pRb dependent targets described. This hypothesis is further supported by the detection of E7 oligomers in the cytosol of cancerous cells from tissue biopsies.